Religion and dialogue in the city: case studies on interreligious encounter in urban community and education - Ipgrave, Julia; Knauth, Thorsten; Körs, Anna; Vieregge, Dörthe (Religious diversity and education in Europe, 2018)
Urban spaces throughout Europe are increasingly characterised by a mixture of different religions and worldviews. Being home to a wide range of religious and non-religious groups and individuals does not mean that cities are automatically also spaces of interreligious and interfaith encounters. Whether a city is a venue for interreligious encounter and dialogue, or merely a place where various religions and worldviews exist side by side, is a central question for the continuing social cohesion of modern societies. This volume presents selected findings of the international research project ‘Religion and Dialogue in Modern Societies’ (ReDi) which investigated dialogical practice in the five metropolitan cities Oslo, Stockholm, London, Hamburg and Duisburg. It offers a range of case studies addressing two fields of activity: dialogue and interreligious encounters in the urban space and dialogue in education.